Ethnic Plants of Tharu Community of Eastern Nepal - Chaudhary, Sujan; Magar, Gyanu Thapa; Sah, Shiv Nandan; Parajuli, Sanju (International Journal of Applied Sciences and Biotechnology, 2020)
Ethnobotany is the study of ethnic plants of particular people living in particular place. It accommodates list, details and description of all those studied plants regarding with their various uses. Tharu people belong to one of the indigenous communities especially in Terai region of Nepal. Tharu people have been using these plant resources since 18th century. This study aims to identify ethnic plants of Tharu community of eastern Nepal and their uses in their daily lives.  Enumeration of useful plants from Tharu ethnic community was conducted in four villages of Ramdhuni municipality of Sunsari district. Participatory Rural Appraisal (PRA) and household sampling technique were used for data collection. Plant specimens were collected and information regarding it was obtained from local Dhamis, Jhankris, farmers and old age people. This study reported thirty-seven useful plant species under 25 families. In total 37 species, 25 were recorded as medicinal plant, used to treat pneumonia, menstrual disorder, stones, piles, skin disease etc. Other plant species were used for food, fodder, timber, fiber and ceremonial/ religious activities. Most plant species (78.3%) were having multiple use value, and kept under more than one use category and few species (21.7%) with single use category. Trees (27.02%) and herbs (27.02%), both were dominant over grass, shrubs, climbers and creepers. This study has revealed that many plants species are being used by Tharu community of Eastern Nepal as their ethnic plants for medicine, food, fodder, ornament, material etc which needs to be more explored.Int. J. Appl. Sci. Biotechnol. Vol 8(2): 223-230